The protective effect of the PDE-4 inhibitor rolipram on intracerebral haemorrhage is associated with the cAMP/AMPK/SIRT1 pathway - Dong, Xiao-Liu; Wang, Yan-Hui; Xu, Jing; Zhang, Nan (Scientific reports, 2021)
Rolipram specifically inhibits phosphodiesterase (PDE) 4, thereby preventing inactivation of the intracellular second messenger cyclic adenosine monophosphate (cAMP). Rolipram has been shown to play a neuroprotective role in some central nervous system (CNS) diseases. However, the role of PDE4 and the potential protective effect of rolipram on the pathophysiological process of intracerebral haemorrhage (ICH) are still not entirely clear. In this study, a mouse model of ICH was established by the collagenase method. Rolipram reduced brain oedema, blood–brain barrier (BBB) leakage, neuronal apoptosis and inflammatory cytokine release and improved neurological function in our mouse model of ICH. Moreover, rolipram increased the levels of cAMP and silent information regulator 1 (SIRT1) and upregulated the phosphorylation of AMP-activated protein kinase (AMPK). Furthermore, these effects of rolipram could be reversed by the SIRT1 inhibitor sirtinol. In conclusion, rolipram can play a neuroprotective role in the pathological process of ICH by activating the cAMP/AMPK/SIRT1 pathway.